A freelance-based foreign exchange programme: Tasmanian students' professional development on WORLDREP. (1st June 2019) - Dodd, Bill; Konkes, Claire; Reid, Donald; Lester, Libby
In the context of rapidly changing newsrooms and a constriction in entry-level positions for graduates, the Europe and Australia in the World (WORLDREP) programme seeks to prepare students by pairing freelance journalism with overseas training and exchange. However, the entrepreneurial focus of the course must be weighed against the challenges and idiosyncratic hiring criteria that graduates face on their return home. This article discusses interviews with former Tasmanian participants to compare what the students felt they acquired during the course with perceived barriers and challenges post-graduation. We find that the programme's freelance focus cultivates a range of applied skills, an extensive publication portfolio and professional confidence. However, interviewees also reported that a lack of local newsroom contacts ‐ traditionally provided through newsroom internships ‐ constitutes a hurdle on their return home. This prompts a discussion about how to complement exchange programmes with local networking and professional development initiatives that can ground what students have learnt overseas in local journalism practice.